2021
DOI: 10.34067/kid.0004142020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients with CKD in New York City

Abstract: Background: Coronavirus disease 2019 (COVID-19) has affected millions of people, and several chronic medical conditions appear to increase the risk of severe COVID-19. However, our understanding of COVID-19 outcomes in patients with chronic kidney disease (CKD) remains limited. Methods: This was a retrospective cohort study of patients with and without CKD consecutively admitted with COVID-19 to three affiliated hospitals in New York City. Pre-COVID-19 CKD diagnoses were identified by billing codes and verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Prior studies have shown higher SARS-CoV-2 mortality among hospitalized older adults with CKD, and among nursing home residents with kidney failure or renal insufficiency documented in the MDS. 2,6,9 Our study corroborates and expands upon these findings by using creatinine-based determination of CKD stage, allowing a more granular assessment of how CKD at different stages is associated with mortality.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 77%
See 1 more Smart Citation
“…Prior studies have shown higher SARS-CoV-2 mortality among hospitalized older adults with CKD, and among nursing home residents with kidney failure or renal insufficiency documented in the MDS. 2,6,9 Our study corroborates and expands upon these findings by using creatinine-based determination of CKD stage, allowing a more granular assessment of how CKD at different stages is associated with mortality.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 77%
“…[1][2][3][4] Independently, chronic kidney disease (CKD) is a significant predictor of mortality in nursing home residents with SARS-CoV-2, 2,3 as well as in the general population. [4][5][6][7][8][9] However, the relationship between CKD stage and SARS-CoV-2 mortality has not been explored among nursing home residents. We described the association between CKD stage and all-cause 30-day mortality following SARS-CoV-2 diagnosis among nursing home residents.…”
Section: To the Editormentioning
confidence: 99%
“…CKD is an independent risk factor for COVID-19-associated in-hospital mortality in elderly patients, and acute-on-chronic kidney injury increases the odds of in-hospital mortality in patients with CKD hospitalized with COVID-19 [ 44 ]. A study showed that compared with patients without preexisting CKD, dialysis patients had a higher risk for 28-d in-hospital death, whereas patients with non-dialysis-dependent CKD had an intermediate risk [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies analyzed the relation between pre-existing renal disease and worse outcome in the form of higher mortality [19][20][21], need for hospitalization, and intensive care admission in patients with SARS-CoV2 infection [22]. A propensity-score match study conducted in a multicenter study of electronic medical records in a cohort of 152,463 patients found that any grade and in particular moderate chronic kidney disease (CKD) was an independent risk factor for more severe COVID-19 disease presentation and mortality, after accounting for other coexistent comorbidities [23].…”
Section: Renal Disease In Covid-19mentioning
confidence: 99%